Contratos de franquia: da inaplicabilidade do Código de Defesa do Consumidor na relação estabelecida entre franqueador e franqueado - Urbanez, Alessandra (2016)
This study focuses on whether - or not - the application of the Consumer Protection Code to franchise agreements. The established relationship between franchisor and franchisee is consumption in order to justify the incidence of the protective rules of the consumerist code? What does the doctrine and what have been the decisions of the courts of the various states and the High Court of Justice on the matter? Starting from a discussion of the franchise institute and discoursing about its historical and etymological origin, definition, legal nature and species; we will continue with a study on the establishment of the Consumer Protection Code and situations that enable the application of its rules. Finally, we will discuss jurisprudence of the Courts and the Superior demonstrating what has been the positioning of these front of the subject